Thinness and fecundability: Time to pregnancy after adolescent marriage in rural Bangladesh. Issue 3 (24th March 2020) - Hur, Jinhee; West, Keith P.; Shamim, Abu Ahmed; Rashid, Mahbubur; Labrique, Alain B.; Wu, Lee S.F.; Ali, Hasmot; Ullah, Barkat; Schulze, Kerry J.; Klemm, Rolf D.W.; Christian, Parul
Abstract: Undernutrition may affect fecundability, but few studies have quantified this relationship. In rural Bangladesh, where newlywed couples face strong pressures to become pregnant, we assessed fecundability, estimated by time to pregnancy (TTP), and its association with preconceptional thinness among nulligravid, newlywed female adolescents. During 2001–2002, 5, 516 newlywed women aged 12–19 years participated in a home‐based, 5‐weekly surveillance system for 5–6 years to enrol pregnant women into an antenatal vitamin A or β‐carotene supplementation trial. Thinness was defined as a left mid‐upper arm circumference (MUAC) ≤21.5 versus >21.5 cm. At each visit, staff obtained a monthly history of menstruation. Report of amenorrhea prompted a human chorionic gonadotropin urine test to confirm pregnancy. We derived hazard ratios (with 95% confidence intervals [CI]) for pregnancy and Kaplan–Meier curves for TTP. Ages of women at marriage and pregnancy detection (mean ± standard deviation) were 15.3 ± 1.9 and 17.0 ± 1.9 years, respectively. A total of 82.7% of thinner and 87.3% of better nourished women became pregnant. The unadjusted and multivariable relative hazard of ever becoming pregnant was 0.84 (95% CI [0.78, 0.89]) and 0.86 (95% CI [0.81, 0.92]), respectively, and TTP was 12 weeks longer (median [95% CI]: 63 [58–68] vs. 51 [49–54]) in women whose MUAC was ≤21.5 versus >21.5 cm. In rural Bangladesh, thin adolescent newlywed girls have a lower probability of becoming pregnant and experience a longer time to pregnancy.